2020
DOI: 10.1111/myc.13080
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of transient receptor potential melastatin 1 correlate with voriconazole‐related visual adverse events

Abstract: Background: Causes of voriconazole-related visual adverse events (VVAE) remained controversial.Objectives: We aimed to explore the relationship between voriconazole serum concentrations and VVAE as well as the potential influence of transient receptor potential melastatin 1 (TRPM1) on VVAE.Patients/methods: This prospective observational cohort study was done in two stages. Patients who received voriconazole for invasive fungal diseases were consecutively enrolled. Correlations between voriconazole trough leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Besides, the visual disturbances associated with voriconazole are likely due to block of transient receptor potential melastatin 1 (TRPM1) channels in retinal ON-bipolar cells [44]. Jiang et al [45] reported the TRPM1 genetic polymorphisms correlated with voriconazole-related visual adverse events. All those situations might influence the relationship between CYP2C19 polymorphisms and neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the visual disturbances associated with voriconazole are likely due to block of transient receptor potential melastatin 1 (TRPM1) channels in retinal ON-bipolar cells [44]. Jiang et al [45] reported the TRPM1 genetic polymorphisms correlated with voriconazole-related visual adverse events. All those situations might influence the relationship between CYP2C19 polymorphisms and neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Jiang et al . [45] reported the TRPM1 genetic polymorphisms correlated with voriconazole-related visual adverse events. All those situations might influence the relationship between CYP2C19 polymorphisms and neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%